Effect of enzymes addition on the total tract apparent digestibility of piglet diets Efeito da adição de enzimas na digestibilidade total aparente de dietas para leitões desmamados - Barros P.C. (2014)
The experiment was realized to evaluate the effect of inclusion of amylase and protease alone or in combination on digestibility of piglets diets contend hard-endosperm corn. Sixteen castrated piglets weaned at 25 days were individually penned in metabolic crates and distributed in four diets using a balanced two period changeover design. The experimental diets were isonutritive and supplemented with 0.06% of amylase and 0.012% of protease alone or in combination. The results showed the amylase or protease alone or in combinations had no influence (P>0.05) on coefficients of digestibility in none of the two periods studied. The average of coefficients of digestibility were 87.9, 88.2, 85.3, 77.7, 97.3, and 90.9% to dry matter, organic matter, crude protein, ash, starch and gross energy, respectively. In conclusion, addition of amylase and protease alone or in combination have no influence on digestibility of piglets diets contend hard-endosperm corn.